Impact of Tree Canopy Elevation on Rainfall Attenuation and Soil Erosion Dynamics for Enhanced Erosion Control - Khwaja Mir Tamim Haqdad; Yoshifumi Satofuka; Masamitsu Fujimoto; Masahiro Murata (Journal of the Civil Engineering Forum)
Afforestation harvesting operations and the interception processes of tree canopies profoundly impact rainfall intensity attenuation, thereby altering both the magnitude and intensity of rainfall, which leads to changes in the production of runoff and sediment. Concurrently, the kinetic energy (KE) of raindrops is moderated by the presence of the canopy, with heightened attenuation observed during the canopy’s full leaf-out phase. This attenuation of rainfall intensity under different tree canopy elevations, resulting from the dynamic interaction between rainfall and the tree canopy, is a fundamental component of the interception process, influencing water distribution and soil stability. This study evaluates the impact of rainfall interception by canopies of six trees of the same species at varying elevations (H1=5.90 m, H2=5.68 m, M1=4.02 m, M2=4.04 m, L1=2.19 m, L2=2.33 m) on soil erosion dynamics. A controlled experiment in the woodland of Ritsumeikan University involved plastic boxes (37 cm25 cm) placed under each canopy, filled with decomposed granite and silica sand, and set on a 20° slope. The experiment measured soil displacement within a designated erosion area (6 cm 15 cm) in the boxes following three rainfall events with different durations and precipitation levels. Results showed that the eroded soil mass (measured in grams) in the boxes was lower at the lower elevation sites (L1 and L2) compared to the medium and higher canopy elevations (M1, M2, H1, and H2). Lower tree canopies not only attenuate raindrop KE but also enhance rainfall redistribution, increase litter-induced surface roughness, improve infiltration, and reduce runoff-driven erosion. Their proximity to the soil enhances microclimatic regulation, minimizing sediment detachment and transport.